Kvantitativni model vrednotenja geodiverzitete na podlagi raznolikosti in gostote elementov geodiverzitete na primeru kontaktnega krasa med Kočevsko Reko ter Kostelom - Stefanovski, Sašo (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2020)
The article presents a new objective systematic approach for geodiversity evaluation in the study area between Kočevska Reka and Kostel. The method is based on spatial diversity and density of geodiversity elements while terrain ruggedness is also taken into account. It was used on a contact karst area, where geodiversity hotspots were identified. The method was evaluated as appropriate for geodiversity evaluation.
Keywords: digital elevation model; digitalni model višin; Dinarski kras; geodiversity; geodiverziteta; geomorfologija; geomorphology; karstology; krasoslovje; Slovenia; Slovenija